2021
DOI: 10.3389/fimmu.2021.778455
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Acetylsalicylic Acid Reduces T Cell Immune Activation: Potential Implications for HIV Prevention

Abstract: IntroductionAcetylsalicylic acid (ASA) is a well-known and safe anti-inflammatory. At low-dose, it is prescribed to prevent secondary cardiovascular events in those with pre-existing conditions and to prevent preeclampsia. Little is known about how low-dose ASA affects the immune response. In this study, we followed women to assess how ASA use modifies T cells immune phenotypes in the blood and at the genital tract.MethodsHIV uninfected women from Kenya were enrolled in this study and followed for one month to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Leukocyte‐derived EV concentrations may reflect the fact that aspirin at low doses is able to inhibit innate immune‐mediated responses, by reducing the frequency of activated CD4+ T cells 47 . It is also well known that low doses of aspirin ameliorate endothelial function, improving vasodilation, reducing thrombosis, and inhibiting atherosclerosis 48,49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leukocyte‐derived EV concentrations may reflect the fact that aspirin at low doses is able to inhibit innate immune‐mediated responses, by reducing the frequency of activated CD4+ T cells 47 . It is also well known that low doses of aspirin ameliorate endothelial function, improving vasodilation, reducing thrombosis, and inhibiting atherosclerosis 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…38,46 Leukocyte-derived EV concentrations may reflect the fact that aspirin at low doses is able to inhibit innate immune-mediated responses, by reducing the frequency of activated CD4+ T cells. 47 It is also well known that low doses of aspirin ameliorate endothelial function, improving vasodilation, reducing thrombosis, and inhibiting atherosclerosis. 48,49 Since the concentrations of endothelial-derived EVs exposing PS were significantly lower at T10 vs. T24, suggesting lower endothelial cell apoptosis, it is intriguing to speculate that low doses of aspirin shift such a balance toward the antiapoptotic side for the endothelial compartment, also influencing the release of EVs.…”
Section: Articlementioning
confidence: 99%
“… 24 We recently found that this mechanism is linked with the immune-directed activities of aspirin in experimental chronic inflammation. 25 Although aspirin has been shown to reduce aspects of systemic inflammation and immune activation in healthy volunteers, 26 , 27 aspirin did not reduce biomarkers of HIV-related immune activation in PWH receiving ART in a placebo-controlled trial. 28 Furthermore, in PWH on ART, the effects of aspirin on the inhibition of platelet activation are impaired.…”
Section: Introductionmentioning
confidence: 98%